2021
DOI: 10.1101/2021.10.28.466258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA methylation patterns differ between free-living Rhizobium leguminosarum RCAM1026 and bacteroids formed in symbiosis with pea (Pisum sativum L.)

Abstract: Rhizobium leguminosarum (Rl) is a common name for several genospecies of rhizobia able to form nitrogen-fixing nodules on the roots of pea (Pisum sativum L.) and undergo terminal differentiation into a symbiotic form called bacteroids. In this work, we compared the genomes of the free-living and differentiated forms of the Rl strain RCAM1026 using Oxford Nanopore long reads. No significant genome rearrangements were observed, but the relative abundances of replicons were different between the cell states. GANT… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…at the operon-level) (Hale, van der Woude, and Low 1994), or even for a single site (Birkholz et al 2022). One exception to this is a recent study, which suggested that genome-wide DNA methylation patterns differ between free-living and terminally differentiated bacteroids of the soil bacterium Rhizobium leguminosarum (Afonin et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…at the operon-level) (Hale, van der Woude, and Low 1994), or even for a single site (Birkholz et al 2022). One exception to this is a recent study, which suggested that genome-wide DNA methylation patterns differ between free-living and terminally differentiated bacteroids of the soil bacterium Rhizobium leguminosarum (Afonin et al 2021).…”
Section: Introductionmentioning
confidence: 99%